Studi Hasil Pelatihan Analisis Video dan Tool Pemodelan Tracker pada Guru MGMP Fisika Kabupaten Agam - Asrizal, Asrizal; Yohandri, Yohandri; Kamus, Zulhendri (JURNAL EKSAKTA PENDIDIKAN (JEP), 2018)
Experiment is important in physics to explain and describe a physical phenomenon and its characteristics. For this reason physics teachers should conduct the physics experiment activities to motivate students in learning and to improve scientific process skills, scientific attitudes, and student understanding in physics learning. However, in the experiment activities of physics were found many problems such as experiment equipment was insufficient, there is no equipment, equipment canât operated well, and so on. An alternative solution to solve this problem was to do the video analysis and modeling tool tracker on physics teacher. The purpose of this research was to investigate the effects of the implementation the tracker video analysis and modeling tool on physics teachers. The research design was pretest and postest for one group sample. The sample of research was 26 physics teachers of Physics MGMP teacher in Agam district of West Sumatera. Instruments to collect the data consist of pretest and postest sheet, performance assessment sheet of video analysis product and questionnaires sheet of physics teachers. Data analysis techniques include descriptive statistical analysis, normality test, homogeneity test and paired comparison test for one group sample. From the data analysis, it can be stated that: 1). the average value of video analysis products from physics teachers is 85.10 and this value can be classified into very good category, 2). the average value of responses of physics teachers on training implementation of video analysis and tool modeling is 73.81 and this average value can be grouped into good category, and 3). the implementation of video analysis training of object motion video by using tracker software is effective to improve the understanding the physics MGMP teachers in Agam district on learning material of tracker video analysis and modeling tool, but the average value of understanding still in the low category.